2008
DOI: 10.1177/0960327107082224
|View full text |Cite
|
Sign up to set email alerts
|

CYP2A6 activity in a healthy Spanish population: effect of age, sex, smoking, and oral contraceptives

Abstract: This study was performed to assess the influence of age, sex, smoking, and contraceptive use on CYP2A6 activity. In the metabolism of caffeine, the conversion of 1,7 dimethylxanthine (17X) to 1,7 dimethiylurate (17U) is catalyzed primarily by CYP2A6. CYP2A6 phenotype was determined by the urinary ratio 17U:17X in the interval of 4–5 h after caffeine intake in 179 healthy white Spaniards (102 women and 76 men). There were 99 non-smokers and 80 smokers. Among women, 26 were taking oral contraceptives. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 38 publications
4
18
0
2
Order By: Relevance
“…So far, higher enzyme activity in women compared to men was observed in European-Americans, 9,18,23) Africans, 20,31) Spanish, 18,21) British, 12) and Thais. 6) Some of the previous studies also reported increased enzyme activity in OC users, 21,23) suggesting estrogen as the mechanism of CYP2A6 induction in women. 23) Yet, the findings on association between CYP2A6 and sex were not always consistent, as no significant sex differences in enzyme activity was discovered in Chinese, 42) Greeks, 26) Serbs, 22) or Caucasians in general.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…So far, higher enzyme activity in women compared to men was observed in European-Americans, 9,18,23) Africans, 20,31) Spanish, 18,21) British, 12) and Thais. 6) Some of the previous studies also reported increased enzyme activity in OC users, 21,23) suggesting estrogen as the mechanism of CYP2A6 induction in women. 23) Yet, the findings on association between CYP2A6 and sex were not always consistent, as no significant sex differences in enzyme activity was discovered in Chinese, 42) Greeks, 26) Serbs, 22) or Caucasians in general.…”
Section: Discussionmentioning
confidence: 96%
“…CYP2A6 enzyme activity can be determined by several phenotyping strategies, including coumarin, 6,25) nicotine, 13,31) cotinine, 38) and caffeine 21,22) methods. In the present study, we used caffeine as a probe drug, and estimated enzyme activity using the urine 17X/ 17U ratio as an index.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also evidence for higher CYP2A6 activity in women (Sinues et al, 2008), although that could, in part, reflect the use of estrogen-containing contraceptives, given the estrogen responsiveness of the human CYP2A6 gene (Higashi et al, 2007). CYP1A2 substrates, including caffeine and the antipsychotic agents olanzapine and clozapine, show higher clearance rates in men (Schwartz, 2007).…”
Section: Sex Differences In Hepatic Drug Metabolismmentioning
confidence: 99%
“…Moreover, CYP2A6 enzyme activity appears to be affected by concomitant drug use, including rifampicin, dexamethasone, phenobarbital, and ketokonazole Tomaszewski et al, 2008) CYP2A6 enzyme activity display pronounced inter-ethnic variations between African Americans, Asians, and Caucasians (Djordjevic et al, 2010;Kandel et al, 2007;Nakajima et al, 2006), and CYP2A6 genetic variation is commonly considered as the major cause for the observed differences. Various factors such as ethnicity (Djordjevic et al, 2010(Djordjevic et al, , 2013Kandel et al, 2007;Nakajima et al, 2006), genotype Pitarque et al, 2004), sex (Kandel et al, 2007;Mwenifumbo et al, 2007), age ( Johnstone et al, 2006;Sinues et al, 2008), cigarette smoking (Djordjevic et al, 2010;Mwenifumbo et al, 2007), and oral contraceptive use (Sinues et al, 2008) are reported to influence CYP2A6 enzyme activity. However, such findings are often inconsistent (Begas et al, 2007;Djordjevic et al, 2010;Kadlubar et al, 2009;Mahavorasirikul et al, 2009), warranting further investigations.…”
Section: Introductionmentioning
confidence: 99%